Adiabatic state preparation of correlated wave functions with nonlinear scheduling functions and broken-symmetry wave functions - Kenji Sugisaki; Kazuo Toyota; Kazunobu Sato; Daisuke Shiomi; Takeji Takui (Communications Chemistry, 2022)
Adiabatic state preparation (ASP) can generate correlated wave functions for quantum chemical calculations, but is inherently unsuitable for studying strongly correlated systems. Here, the authors perform numerical simulations of ASP for the ground state wave functions of molecules with strongly correlated electrons and propose practical conditions for preparation of close-to-exact correlated wave functions.